New approaches to vocational education in Europe : the construction of complex learning-teaching arrangements - Mulder, Regina H. [Herausgeber]; Sloane, Peter F. E. [Herausgeber] (Symposium Books, 2004)
This publication represents the result of joint research funded by the COST (European Cooperation in the field of Scientific and Technical Research) programme. Action A11 investigated the concept of complex learning-teaching arrangements. The papers collected in this volume emerged from the efforts of working group three, whose research into this concept was completed in 2002. Complex learning-teaching arrangements aim to prepare students for work and lifelong learning in an environment where they will have to cope with complex work situations. "he working group aimed to develop approaches to training to achieve this goal and their work derived certain characteristics required within such learning-teaching arrangements. The first part provides an overview of general themes connected with the concept and its theoretical background of the concept. The second part demonstrates how the idea of complex learning-teaching environments influences the particular training contexts in different countries. (BIBB-Doku)

Part one "General prospects" contains the following chapters: Constructivist learning theories and complex learning environments / Robert-Jan Simons & Sanneke Bolhuis (p. 13-25); A comparison of VET structures in Germany and England: contexts of complex teaching-learning arrangements / Hubert Ertl & Peter F. E. Sloane (p. 27-43); Deconstructing apprenticeship learning: what factors affect its quality / Michael Eraut (p. 45-57); Conditions for instructional design and innovation in vocational education: successful design and implementation of complex learning environments / Regina H. Mulder (p. 59-70); New technologies and complex teaching-learning arrangements / H.-Hugo Kremer (p. 71-80). Part two "Case studies" contains the following chapters: The advantages and disadvantages of learning and teaching in a practice firm / Franz Gramlinger (p. 81-90); Learning in complex environments: continuous quality improvement in practice firms / Michaela Trummer (p. 91-101); Teaching intercultural competence: a simulation / Susanne Weber (p. 103-114); Mastery learning in and by complex teaching-learning environments / Frank Achtenhagen (p. 115-129); Focus groups as an instrument for the implementation of didactic innovation: concepts and experience / H. -Hugo Kremer (p. 131-139); The application transfer between schools and enterprises in the German dual system: putting it into practice (p. 141-155); From business to game / Fabrice Hoff (p. 157-169); Design and evaluation of complex learning environments in secondary vocational education / Regina H. Mulder (p. 171-182).
Keywords: L 3 Lehr-Lern-Forschung; L 2 Lehr-Lerngestaltung; L 2.2 Didaktik; I 2.1 Deutschland; I 2.2.1 Westeuropa; Berufsausbildung; Lehr-Lern-Forschung; Lernarrangement; Didaktik; Internationaler Vergleich; Bundesrepublik Deutschland; England; Frankreich; Niederlande; Österreich